Nursing leaders' satisfaction with information systems in the day-to-day operations management in hospital units - Laura-Maria Peltonen; Kristiina Junttila; Sanna Salanterä (Netherlands, 2022)
Information usage in the day-to-day operations management of hospital units is complex due to numerous information systems in use. The aim of this study was to describe and compare nurse leaders' satisfaction with information systems used in the day-to-day operations management in hospital units. The design was a cross-sectional survey with five questions rated from one (disagree) to five (fully agree). The response rate was 65 % (n = 453). Respondents reported fair satisfaction with how information systems support decision-making (median 4, IQR 3–4) and improve ease of access to information (median 4, IQR 3–4). However, respondents were less satisfied with how systems improve speed of access to information (median 3, IQR 3–4). Nor did respondents think that systems were developed for them (median 3, IQR 2–4). Respondents further reported needing numerous systems daily to support decision-making (median 4, IQR 3–5). A clear need for one system, which would gather important information for display was stated (median 5, IQR 4–5). Work experience, gender and time when overseeing the unit were associated with some aspects related to satisfaction. In conclusion, information system improvements are needed to better support the day-to-day operations management in hospital units.
Nursing Informatics 2018